A low-concentration eutectic electrolyte for superior cycling ability of aqueous zinc-ion capacitors. Issue 38 (30th August 2022) - Lu, Xuejun; Tao, Li; Qu, Keqi; Zhang, Yue; Liu, Chang; Godin, Robert; Liu, Jian
Abstract : A low concentration eutectic electrolyte (LCEE) proposed by using N -methyl-2-pyrrolidone (NMP) additive delivered superior cycling ability and excellent compatibility in coin cell and pouch cell prototypes. Abstract : Aqueous electrolytes are emerging systems for the development of aqueous zinc-ion capacitors (AZICs). Preferably, the aqueous electrolyte should satisfy low consumption of organic Zn salts, high electrochemical stability of limited free-water activity, and an environmental-friendly feature. Particularly, a eutectic electrolyte possesses unique features of non-flammability, structural flexibility, and good thermal and chemical stability, benefiting from the strong intermolecular interaction among the eutectic components. Herein, a low concentration eutectic electrolyte (LCEE) was proposed by introducing N -methyl-2-pyrrolidone (NMP) additive in a 2 m aqueous Zn(OTf)2 solution, where NMP participated well in the formation of eutectic-NMP complexes and [Zn(H2 O)4 NMP] 2+ ion complexes. The optimal electrolyte of Z1 W-0.2NMP exhibited ultra-long cycling stability, e.g., 100% and ∼95% capacitance retention over 50 000 cycles at 4 A g −1 and 100 000 cycles at 8 A g −1, respectively. The assembly of Z1 W-0.2NMP in coin cells (CR2032) not only demonstrated a high capacitance of 275.3 F g −1 at 0.5 A g −1 but also possessed a high energy density of 275.3 W h kg −1 with a power density of 101 kW kg −1 . Ultimately, pouch-cell prototypes using Z1 W-0.2NMP electrolyte displayed attractive compatibility and stability ( i.e., with a high capacitance retention of ∼90% after 4500 cycles at 2 A g −1 ). This work is expected to stimulate the design and practical implementation of AZICs and other electrochemical energy storage devices.